Addressing the unfulfilled codex standard for honey for stingless bee honey through lyophilization. Issue 2 (4th March 2022) - Yong, Chin-Hong; Muhammad, Syahidah Akmal; Fadhullah, Widad; Hassan, Hasnuri Mat; Mohd Rodhi, Ainolsyakira; Mustafa, Mohd Zulkifli; Kelly, Simon D.
ABSTRACT: Some studies have found that the nutritional values of stingless bee honey (SBH) may be similar if not more than normal honey, prompting the Malaysian government to promote it as a superfood. However, SBH does not fulfil the Codex Standard for Honey (CODEX STAN 12-19811) in terms of moisture content and the lack of protein to be analysed with Internal Standard Carbon Isotope Ratio Analysis (ISCIRA). Hence, a lyophilization process was introduced prior to stable carbon isotope analysis of SBH to address both of these issues. It was found that once moisture content was decreased to a level below 20 % for 19 SBH samples, the percentage increment of protein extracted from the samples varied between 6 and 385 % relative to protein extracted from SBH before lyophilization with nine samples found to be adulterated. Caution is necessary when lyophilizing the SBH as significant isotope shifts were seen for SCIRA and ISCIRA values. Nevertheless, the carbon isotope shifts did not change the final outcome of the 'pass' or 'fail' of the adulteration result. Overall, the removal of water from SBH is required but caution is necessary as carbon isotope shifts were observed as SBHs underwent the lyophilization process.